Maintenance management proposal based on reliability to reduce machinery failures of the broiler line in a poultry company de Perú (LACCEI, 2024)
The main objective of the research is to propose maintenance management based on reliability to reduce failures of the machinery of the broiler line of a poultry company. For this reason, maintenance management techniques were applied: criticality analysis of machines or processes, fault tree, mode effect analysis and failures (AMEF). For this reason, the objective of this thesis was to develop a preventive maintenance management plan based on Reliability (RCM), which yielded the following results: failures were reduced by 66%, as a result, availability increased from 86% to 96%, in the AMEF the NPR decreased by 65% ​​with the application of the maintenance strategies proposed for each potential failure mode, the implementation of the reliability-based maintenance management plan resulted in annual savings of 75,799.17 soles due to the reduction of machinery failures.